Identification of psl, a Locus Encoding a Potential Exopolysaccharide That Is Essential for Pseudomonas aeruginosa PAO1 Biofilm Formation - Jackson, Kara D. (American Society for Microbiology, 2004)
Bacteria inhabiting biofilms usually produce one or more polysaccharides that provide a hydrated scaffolding to stabilize and reinforce the structure of the biofilm, mediate cell-cell and cell-surface interactions, and provide protection from biocides and antimicrobial agents. Historically, alginate has been considered the major exopolysaccharide of the Pseudomonas aeruginosa biofilm matrix, with minimal regard to the different functions polysaccharides execute. Recent chemical and genetic studies have demonstrated that alginate is not involved in the initiation of biofilm formation in P. aeruginosa strains PAO1 and PA14. We hypothesized that there is at least one other polysaccharide gene cluster involved in biofilm development. Two separate clusters of genes with homology to exopolysaccharide biosynthetic functions were identified from the annotated PAO1 genome. Reverse genetics was employed to generate mutations in genes from these clusters. We discovered that one group of genes, designated psl, are important for biofilm initiation. A PAO1 strain with a disruption of the first two genes of the psl cluster (PA2231 and PA2232) was severely compromised in biofilm initiation, as confirmed by static microtiter and continuous culture flow cell and tubing biofilm assays. This impaired biofilm phenotype could be complemented with the wild-type psl sequences and was not due to defects in motility or lipopolysaccharide biosynthesis. These results implicate an as yet unknown exopolysaccharide as being required for the formation of the biofilm matrix. Understanding psl-encoded exopolysaccharide expression and protection in biofilms will provide insight into the pathogenesis of P. aeruginosa in cystic fibrosis and other infections involving biofilms.